Development of POGIL Based Calculus Module for Informatics Engineering Students - Weni Gurita Aedi; Lisda Fitriana Masitoh (STKIP Singkawang, 2020)
The purpose of this study was to develop a calculus learning module based on POGIL for Informatics Engineering students. The POGIL-based module contains namely exploring, discovering, and applying. Through POGIL, students are more responsible for their educational assignments, learn to rely on their ability to think rather than just remember and develop positive relationships with other students. The module was developed and contains the POGIL syntax. The quality of development results is determined based on Nieveen's criteria, namely valid, practical, and effective. This is a Research and Development Study that applies the Plomp Model which consists of the initial research, development, and assessment phases. The subjects of this research were students of Informatics Engineering at the University of Pamulang. The research instruments used were validation sheets, student assessment questionnaires, and calculus questions. In terms of validity, based on the assessment conducted by experts, has met the valid criteria with a very good category with an empirical score that is 312. In terms of practicality, based on the results of student assessments after participating in learning using the developed tools, it is in the very good category with an empirical score of 1924. In terms of effectiveness, the result is Z = 1.75 > Z_a = 1.645, so Ho is rejected, which means that the proportion of students who score 70 is more than 74.99%. The results showed that the calculus learning module met the criteria of validity, practicality, and effectiveness.